2013
DOI: 10.1002/hep.26278
|View full text |Cite
|
Sign up to set email alerts
|

SIRT2 overexpression in hepatocellular carcinoma mediates epithelial to mesenchymal transition by protein kinase B/glycogen synthase kinase-3β/β-catenin signaling

Abstract: Sirtuin 1 (SIRT1) has been implicated in telomere maintenance and the growth of hepatocellular carcinoma (HCC). Nevertheless, the role of other sirtuins in the pathogenesis of HCC remains elusive. We found that sirtuin 2 (SIRT2), another member of the sirtuin family, also contributes to cell motility and invasiveness of HCC. SIRT2 is up-regulated in HCC cell lines and in a subset of human HCC tissues (23/45). Up-regulations of SIRT2 in primary HCC tumors were significantly correlated with the presence of micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
145
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(154 citation statements)
references
References 46 publications
7
145
2
Order By: Relevance
“…SIRT1 is essential for proliferation and telomere maintenance (19), whereas SIRT2 mediates the epithelial-mesenchymal transition (EMT) of cancer cells (20). In the present study, we found that SIRT6 was upregulated in a subset of HCC tissues and cell lines.…”
Section: Introductionsupporting
confidence: 51%
“…SIRT1 is essential for proliferation and telomere maintenance (19), whereas SIRT2 mediates the epithelial-mesenchymal transition (EMT) of cancer cells (20). In the present study, we found that SIRT6 was upregulated in a subset of HCC tissues and cell lines.…”
Section: Introductionsupporting
confidence: 51%
“…Previous studies demonstrated that Akt activation inhibits GSK-3b activity, leading to activation of Wnt/b-catenin signaling and the development of stem-like traits and tumor aggressiveness (19,20). Notably, after overexpression of miR-644a in ESCC cells, the levels of PITX2, p-Akt, p-GSK-3b (inactive form) and active-b-catenin were all reduced (Fig.…”
Section: Mir-644a Inhibits Akt/gsk-3b/b-catenin Pathway By Targeting mentioning
confidence: 79%
“…14) In contrast, growing evidence suggests that SIRT2 promotes tumorigenesis. [15][16][17][18][19] The reason for this discrepancy is unknown, but it may depend on cancer progression stage or cell type. Recent reports using a selective SIRT2 inhibitor demonstrated that SIRT2 inhibition exhibits anti-tumor activity against breast cancer cells by degrading c-Myc oncoprotein.…”
Section: Resultsmentioning
confidence: 99%